Mutations in eukaryotic release factors 1 and 3 act as general nonsense suppressors in Drosophila. - Chao, A.T.; Dierick, H.A.; Addy, T.M.; Bejsovec, A. (Genetics, 2003)
In a screen for suppressors of the Drosophila wingless(PE4) nonsense allele, we isolated mutations in the two components that form eukaryotic release factor. eRF1 and eRF3 comprise the translation termination complex that recognizes stop codons and catalyzes the release of nascent polypeptide chains from ribosomes. Mutations disrupting the Drosophila eRF1 and eRF3 show a strong maternal-effect nonsense suppression due to readthrough of stop codons and are zygotically lethal during larval stages. We tested nonsense mutations in wg and in other embryonically acting genes and found that different stop codons can be suppressed but only a subset of nonsense alleles are subject to suppression. We suspect that the context of the stop codon is significant: nonsense alleles sensitive to suppression by eRF1 and eRF3 encode stop codons that are immediately followed by a cytidine. Such suppressible alleles appear to be intrinsically weak, with a low level of readthrough that is enhanced when translation termination is disrupted. Thus the eRF1 and eRF3 mutations provide a tool for identifying nonsense alleles that are leaky. Our findings have important implications for assigning null mutant phenotypes and for selecting appropriate alleles to use in suppressor screens.